The role of the pharmaceutical professional in the face of self-medication – Drug intoxication by NSAIDs (Research, Society and Development, 2022)
Medicines play an essential role in health systems, as they save lives and improve health. Non-Steroidal Anti-Inflammatory Drugs - NSAIDs and Analgesics are among the most widely consumed group of drugs worldwide. Anyone who uses any type of medication, whether over-the-counter (OTC) or even with a medical prescription, needs to be aware of the prescribed dosages, as adverse effects can be influenced by several factors, and mainly lead to drug intoxication. Thus, the objective of this study is: to analyze the importance of pharmaceutical assistance in the face of self-medication performed by NSAIDs, such as diclofenac, ketoprofen, and ibuprofen, which represent the highest incidence of intentional poisoning. For this, the qualitative bibliographic method was used, which, through a literature review, used studies published in the period from 2012 to 2022. Therefore, the concept of drug intoxication, the epidemiology of NSAIDs intoxication and the reversals of intoxication were exposed and its treatment. In view of this, it was concluded that in cases of drug intoxication by ANAIs, the victim runs gastrointestinal, cardiovascular, thrombotic, cerebrovascular, renal, gestational and fetal risks, in some cases, leading to death, being of extreme importance the reversal by vein. of gastrointestinal lavage. It was also verified the importance of the pharmaceutical professional in the practice of correct and adequate use of medicines, in order to advise the best way for the use of medicines in the treatment in which the patient is.